Physical And Chemical Properties Of Calcium Nitrite - U.R.Panzhiev; Z.T. Ruzieva; A.Kudratov (International Journal on Orange Technologies, 2023)
The essence of the process of obtaining calcium nitrite is the absorption of nitrous gases, taken after the contact apparatus, with milk of lime with a concentration of 100-140 g/l. The reactions occurring during the absorption of nitrogen oxides by a solution of calcium hydroxide can be represented by the equations